2016
DOI: 10.1002/eco.1720
|View full text |Cite
|
Sign up to set email alerts
|

Effects of root mat buoyancy and heterogeneity on floating fen hydrology

Abstract: Floating fen ecosystems are home to several protected habitats and species. Their development and conservation require special attention regarding water management. Although they are known to be heterogeneous and partially buoyant, their root mats are simulated in hydrological models as homogeneous, static systems. The objective of this study is to quantify root mat heterogeneity and buoyancy and to assess their effects on groundwater flow and transport, and to determine if these factors need to be taken into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 44 publications
1
15
0
Order By: Relevance
“…Literature reports large decreases in the hydraulic conductivity of peat soils as a consequence of increased gas bubble content; Baird and Waldron () report a decrease by a factor two, while Reynolds et al () found a decrease by a factor four. Although the hydraulic conductivity in peat soils can vary greatly due to large variations in peat quality, bulk density, and rate of decomposition (e.g., Boelter, ; Chason & Siegel, ; Stofberg et al, ), gas bubbles may affect the hydraulic conductivity in a wide range of peat soils.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature reports large decreases in the hydraulic conductivity of peat soils as a consequence of increased gas bubble content; Baird and Waldron () report a decrease by a factor two, while Reynolds et al () found a decrease by a factor four. Although the hydraulic conductivity in peat soils can vary greatly due to large variations in peat quality, bulk density, and rate of decomposition (e.g., Boelter, ; Chason & Siegel, ; Stofberg et al, ), gas bubbles may affect the hydraulic conductivity in a wide range of peat soils.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies, however, deal with mineral soils, and little knowledge exists about the effects of salinity on the interaction between biogeochemical processes and the hydraulic conductivity of peat soils. Water flow through wetland sediments is affected by the hydraulic conductivity, which can vary greatly among different types of peat with varying degrees of decomposition (e.g., Boelter, ; Chason & Siegel, ; Stofberg, Van Engelen, Witte, & Van der Zee, ). Laboratory experiments and models (e.g., Comas & Slater, ; Kettridge & Binley, ; Ours, Siegel, & Glaser, ) indicate that increased salinity can increase flocculation of particles such as humic acids in peat soils, causing pore dilation which potentially influences the hydraulic conductivity of peat soils.…”
Section: Introductionmentioning
confidence: 99%
“…We developed a hydrological model to simulate groundwater and soil water dynamics of a floating fen, using hydrological field measurements of a study area in the Netherlands, in combination with data of a previous study (Stofberg et al, 2016). The model was calibrated and validated using groundwater level data that were collected in the field.…”
Section: General Approachmentioning
confidence: 99%
“…At the newly created edge, the vegetation has so far remained ombrotrophic. The root mat material consists of peat in various stages of humification, as described in Stofberg et al (2016). The topography was determined in three transects perpendicular to surface water edge, using a level and rod, and the root mat thickness was estimated using augers and a device that can be unfolded after it is pushed into the soft soil, making it possible to feel where the root mat begins when it is pulled upwards.…”
Section: Field Measurementsmentioning
confidence: 99%
See 1 more Smart Citation